2020
DOI: 10.1002/essoar.10503657.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconnection and Dipolarization Driven Auroral Dawn Storms and Injections

Abstract: Jupiter displays many distinct auroral structures, among which auroral dawn storms and auroral injections are often observed contemporaneously. However, it is unclear if the contemporaneous nature of the observations is a coincidence or part of an underlying physical connection. We show six clear examples from a recent Hubble Space Telescope campaign (GO-14634) that each display both auroral dawn storms and auroral injection signatures. We found that these conjugate phenomena could exist during intervals of ei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…Overall, then, we have shown that this dawn storm was associated with significant plasma dynamics and heating in the dawnside middle to outer magnetosphere, likely initiated by reconnection and/or disruption of the azimuthal current. The schematic in Figure 7 shows the expected generation and evolution of the dawn storm, with reconnection at an earlier local time triggering the reconfiguration of field lines as suggested previously (Kimura et al., 2017; Yao et al., 2020). The reconfiguration front rapidly expands radially outward and through local dawn, corresponding to the poleward and noonward expansion of the auroral emission, until most of the dawn outer magnetosphere is reconfigured at the full extent of the dawn storm.…”
Section: Discussionsupporting
confidence: 52%
“…Overall, then, we have shown that this dawn storm was associated with significant plasma dynamics and heating in the dawnside middle to outer magnetosphere, likely initiated by reconnection and/or disruption of the azimuthal current. The schematic in Figure 7 shows the expected generation and evolution of the dawn storm, with reconnection at an earlier local time triggering the reconfiguration of field lines as suggested previously (Kimura et al., 2017; Yao et al., 2020). The reconfiguration front rapidly expands radially outward and through local dawn, corresponding to the poleward and noonward expansion of the auroral emission, until most of the dawn outer magnetosphere is reconfigured at the full extent of the dawn storm.…”
Section: Discussionsupporting
confidence: 52%
“…Based on the final measurement by Cassini, energetic neutral atom enhancements and conjugate periodic enhancements of energetic electrons were observed simultaneously with Saturn's aurora (Radioti et al., 2019). Moreover, at Jupiter, contemporaneous in situ and remote sensing observations from the Juno spacecraft and the Hubble Space telescope allowed to directly connect the latest stage of an auroral dawn storm to energetic electron injection in the middle magnetosphere (Z. H. Yao et al., 2020). These previous studies suggested a close relationship between energetic electrons generated by DFs and auroral intensifications.…”
Section: Discussionmentioning
confidence: 99%
“…Some magnetic field reversals appear to have a helical or loop‐like magnetic field structure that is characteristic of plasmoid events (Vogt et al., 2014). Also seen are magnetic signatures of “dipolarizations,” which are the result of plasma compression due to fast planetward flows in the so‐called “exhausts” emanating from the reconnection sites (Artemyev et al., 2013, 2020; Yao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%